Registration of the Louise‐Penawawa spring wheat recombinant inbred line mapping population. Issue 3 (24th September 2020) - Carter, A.H.; Kidwell, K.K.; DeMacon, V.L.; Shelton, G.B.; Burke, A.B.; Balow, K.A.; Herr, A.
Abstract: The Louise‐Penawawa spring wheat ( Triticum aestivum L.) recombinant inbred line (RIL) mapping population (Reg. no. MP‐13, NSL 535038 MAP) was developed from a cross between the elite soft white spring wheat cultivars 'Louise' and 'Penawawa' at Washington State University. The population is composed of 180 RILs developed through single seed descent from the F2 to the F5 generation. The population and its parents were genotyped using both simple sequence repeat and single‐nucleotide polymorphism marker platforms. Analysis of markers identified 29 linkage groups that located to all 21 wheat chromosomes. The population was initially developed for the study of high‐temperature adult‐plant stripe rust resistance but has since been phenotyped and used to identify Hessian fly resistance, tan spot resistance, polyphenol oxidase activity, vital agronomic traits, and milling and baking quality. Markers have been identified that are closely linked with quantitative trait loci (QTL) that influence these traits. This population has the potential to identify QTL for additional traits of interest. Additionally, lines from this RIL population are well suited to introgress traits of interest as both Louise and Penawawa are commercially released cultivars adapted to a variety of growing regions and conditions.